Human Capital Development and Faculty Members’ Contributions: Array - Atiku, Sulaiman Olusegun; Lawal, Ibrahim Olanrewaju; Gamede, Vangeli (The Journal of Accounting and Management, 2020)
High performance and organisational development can be guaranteed by attracting, developing, and retaining talented employees within an organisation. This study investigated the relationship between Human Capital (HC) development plans and faculty members’ contributions at a Tertiary institution in Lagos. This study explores the mediating influence of HC development programmes on the relationship between HC development plans and faculty members’ contributions. This study adopted a survey research design. A quantitative approach to data collections and analysis procedures was adopted for this study. Data was collected from selected faculty members of a higher education institution in Lagos metropolis using a simple random sampling technique. 306 self-administered questionnaires were distributed to the respondents at the institution. Three hypotheses were formulated and tested using inferential statistics via SmartPLS 3.3 software application, which is instrumental in running a Variance-Based Structural Equation Modeling (SEM). The results showed that HC development programmes fully mediate the relationship between HC development plans and faculty members’ contributions. This study submits that adequate funding and proper resources allocation to support smooth implementation of faculty members’ developmental strategies is critical to university performance, in terms of quality of graduates and credible research outputs for national development.